Efforts to Increase Organizational Capacity in Drugs Prevention to the Anti-Drug Youth Core Cadre Organization (KIPAN) Organizations Through Policy Brief Training - Ritonga, Alwi Dahlan; Amin, Muryanto (Talenta Publisher, 2023)
Training and assistance is provided to organizations assigned by KEMENPORA (Ministry of Youth and Sports) to handle drug issues among young people, namely the Anti-Drug Youth Core Cadre Organization (KIPAN). In this training, partners are provided with basic materials (modules) on strategies for making good, correct and appropriate policy recommendations to be implemented by NGOs. Partners receive technical training on policy analysis and how to formulate policy recommendations so that this organization is able to contribute better in dealing with drug problems in North Sumatra. Thus, partners are more aware and understand about the steps that can be taken to overcome the drug problem that exists in North Sumatra. The method used in this service is the Participatory Learning and Action (PLA) method. This service has succeeded in increasing the understanding of as many as 20 training participants about making good and correct Policy Briefs.